Treatment technologies and mechanisms for three odorants at trace level: IPMP, IBMP, and TCA. Issue 3 (1st February 2016) - Li, Xin; Lin, Pengfei; Wang, Jun; Liu, Yuanyuan; Li, Yong; Zhang, Xiaojian; Chen, Chao
Abstract : Odour episodes caused by algal metabolites are gaining more and more attention in recent years. Besides geosmin and 2-methylisoborneol (MIB), 2-isopropyl-3-methoxypyrazine (IPMP), 2-isobutyl-3-methoxypyrazine (IBMP), and 2, 4, 6-trichloroanisole (TCA) have emerged to be important off-flavour sources. Their low odour threshold concentrations (several ng ·L −1 ), which are even lower than those of MIB and geosmin, pose challenges for treatment strategies. Hence, a practical and efficient mitigation technology is needed. The possible practical technologies, including powdered activated carbon (PAC) adsorption and oxidation by chlorine and potassium permanganate, were investigated. The results indicated that chlorine and potassium permanganate oxidation of the three odorants were unfeasible while PAC adsorption was effective. As for adsorption, TCA, followed by IBMP and IPMP, was most easily removed by PAC. The Freundlich model could well describe the adsorption isotherm data. The adsorption capacities for IPMP, IBMP, and TCA were described as follows:, , and . For five earthy/musty odorants including geosmin and MIB, octanol/water partition coefficient, molecular weight, and polarizability all promoted adsorption while aqueous solubility showed a negative influence. The hydrophobic interaction was believed to be the dominant force in the adsorption mechanism while the π -electron interaction enhanced adsorption when a benzene ring was present. This result could be used to predict the adsorption performance of emerging odorants.